ANALISIS PENERAPAN TEKNOLOGI INFORMASI DI PERPUSTAKAAN STMIK PONTIANAK - Anita, Dinda Deby; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research background is because of the research tries to find the applying of information and technology that exist in STMIK Pontianak. The purpose of this research are (1) to know how far the applying of information and technology which has been applied in STMIK Library Pontianak and (2) to find the obctacle that has been faced in the applied of it. The method that has been used in this research is descriptive method by using the qualitative approach, because the researcher think that the problem in this research is complex, so the data that has been collected from the informant must be complete enough by using method that more scientific which by interviewing directly witrh the informant so the data that will be collected is scientific by using approach. The data collection technique are by doing interview, observation, and documentation. The resaearch result shown that the applying of information and technology in STMIK Library Pontianak is already good and already applied in the basic activity that exist in STMIK Library. However, there is something that need to be done in order to improve the information and technology so it can be applied in every activities in there will run well, easy and fast and also can serve the visitors with a good and maximum service quality.Â  Â Keywords: Information and technology, Universitry Library